Protective Factors Associated With Post-traumatic Outcomes in Individuals With Experiences of Psychosis - Campodonico, Carolina; Berry, Katherine; Haddock, Gillian; Varese, Filippo (Frontiers in Psychiatry, 2021)
Trauma and trauma-specific mental health difficulties (e.g., post-traumatic stress disorder) are highly prevalent in people with psychosis. However, not everyone develops post-traumatic symptoms, and some people even experience post-traumatic growth (PTG) following trauma. It is important to identify which protective factors are associated with less severe trauma symptoms and/or positive outcomes to inform the development and implementation of interventions fostering these variables. Eighty-five patients with experiences of psychosis took part in a cross-sectional study. They were administered questionnaires measuring exposure to traumatic events, symptoms of PTSD and complex PTSD and potential protective factors assumed to be associated with lower vulnerability for post-traumatic symptoms and higher post-traumatic growth (trait resilience, secure attachment, social support, adaptive coping, optimism, general self-efficacy). Multiple hierarchical regression showed that some of these protective factors, in particular optimism, were associated with lower post-traumatic symptoms, explaining 21% of the variance in complex PTSD symptoms and 16% of the variance in PTSD symptoms. However, the hypothesised protective factors, in particular resilience and adaptive coping, explained a considerably larger proportion of variance in PTG (44%). Our results suggest that whilst these variables provide only moderate protection from the vulnerability to experience post-traumatic stress, they may play an important role in allowing people to find meaning despite multiple traumas and subsequently lead more fulfilling lives. Therapies targeting the emotional and psychological consequences of trauma in people with psychosis might benefit from the integration of intervention strategies to enhance these additional psychological protective factors, which in turn may lead to positive treatment outcomes beyond the mere reduction of post-traumatic stress symptoms.